Rethinking entrepreneurship theory and research practice: An exploration into alternative theoretical perspectives - Kikooma, Julius (My University, 2010)
Entrepreneurship has been gaining increasing respect from the research community as a field of scholarly study as well as practical application worldwide as a means to achieve wealth creation and personal fulfillment. In Africa, this enthusiasm has, in fact, been matched with calls to scale and mainstream entrepreneurship on the continent. Yet, entrepreneurship, as a theoretical construct and practical phenomenon, remains poorly defined and its interpretation fragmented. This paper reviews and critiques the dominant perspectives on entrepreneurship. It calls into question progress that can be made by continuing to pursue lines of inquiry based on such orthodox perspectives. As away forward, the paper identifies alternative perspectives that have been explored as possible and more fruitful for engaging with the phenomenon.
Keywords: Entrepreneurship theory; research and practice; gender; culture.